MICROSCOPIC AND PHASE ANALYSIS OF CEMENT PASTE CONTAINING WASTE MICRONIZED MARBLE POWDER - Zdeněk Prošek; Pavel Tesárek; Jan Trejbal (Acta Polytechnica CTU Proceedings, 2018)
The article focuses on the impact of waste marble powder on resulting cement composites. We investigate of influence waste marble powder on the hydration process and hence the resulting phase composition. The hydration process was investigated using calorimetry and phase composition of the resulting composite by electron microscopy. The results are compared with a reference sample composed of Portland cement.